A longitudinal critical discourse analysis of ‘immigration’ in the UK parliament - Rade, Rachel E. (2019)
In this thesis, I identify key ideologies and discourses that exist concerning immigration in the UK Parliament, drawing upon a discourse historical approach, as part of an integrated socio-cognitive method of critical discourse analysis. I base my work on a multidisciplinary theoretical framework that incorporates discourse analysis, argumentation theory, social cognition and sociological theories. This longitudinal work, which incorporates both Houses of Parliament, periods of rule by both major parties and an analysis of the speeches of smaller parties, closes a gap in the field, which has previously focused on immigration in the news media and typically within political parties/politicians of the (far-)right.